2021
DOI: 10.3389/fpsyg.2021.576193
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive Reciprocal Obligations: Perceptions of Parental Role in Career Choices of Sub-Saharan African Migrant Youths

Abstract: This study employed interpretivist, grounded theory method and utilized semi-structured interviews to explore how 31 African migrant high school and university students from eight sub-Saharan African representative countries and currently residing in Townsville, Australia, perceived the roles of their parents in their career development. The study findings revealed that the support (financial, social and emotional) and encouragement (sacrificial love, role modeling and guidance) received from parents underpinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Furthermore, according to Tillman (2015), children of educators have a slightly stronger parental influence on their profession choices than is experienced by children of non-educators. Furthermore, Akosah-Twumasi et al (2021) revealed that students had a significant need to acquire parental approval, and that, regardless of whether this permission was obtained early or later, prioritising family demands and commitments was the main focus for all participants. Furthermore, Mtemeri (2020) stated that students are impacted by their friends in a variety of ways when they are making professional decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, according to Tillman (2015), children of educators have a slightly stronger parental influence on their profession choices than is experienced by children of non-educators. Furthermore, Akosah-Twumasi et al (2021) revealed that students had a significant need to acquire parental approval, and that, regardless of whether this permission was obtained early or later, prioritising family demands and commitments was the main focus for all participants. Furthermore, Mtemeri (2020) stated that students are impacted by their friends in a variety of ways when they are making professional decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Tillman (2015) found that children of educators had slightly more parental influence on their profession choices than children of non-educators. According to Akosah-Twumasi et al (2021), students had a significant need to acquire parental approval, and regardless of whether this approval was obtained early or later, prioritising family responsibilities and commitments was the main focus for all participants. Allowing students to negotiate or even override their parents' preferences in choosing a career path may exacerbate the already difficult career decision-making process of young people, particularly if their parents are adamant about maintaining their heritage cultural practices (Akosah-Twumasi et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, for the qualitative phase, a subset of participants had been selected for qualitative interviews based on their attitude scores. To determine the number of subsets of participants that will be Yumnam Surjit Singh, et al / Kuey, 30 (5), xyz selected based on their attitude scores, we established the criteria for selection of the participants who score above a certain threshold on attitude measures; for instance, an attitude score above the 75 th percentile (265.00). The authors then calculate the number of participants who meet this criterion, which yields 214 individuals.…”
Section: Procedurementioning
confidence: 99%
“…The findings of this study have implications for teacher education programs, policy makers, and educational institutions. By understanding student-teachers' Yumnam Surjit Singh, et al / Kuey, 30 (5), 4134 attitudes towards the teaching profession, teachers can adapt programs to better meet the needs and expectations of future teachers, ultimately enhancing the quality of education provided to students. However, there is limited research that comprehensively examines the factors influencing student-teachers' attitudes towards the teaching profession, particularly in the context of teacher education studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although the concept is conceptualized from Chinese culture and applied to describe the relationship between parent-child relationship in Chinese diaspora and East Asian society, similar parent-child relationship patterns are also found in other countries that tend towards collectivism. Countries in Asia, Africa, Latin America, and some parts of Europe with a collectivist identity embody the value of respect and esteem for parents, which is evident in everyday behaviour (Akosah-Twumasi et al, 2021;Kao et al, 2007). It suggests that filial piety is also a value that is important in cultures across the globe.…”
Section: Introductionmentioning
confidence: 99%